Dietary intake of pregnant women and its effect on the birth weight of newborns in rural area of Uttar Pradesh, India - Sahu, Krishna Kumar; Idris, MZ; Agarwal, Monika; Singh, SK; Manar, MK (Asian Journal of Medical Sciences, 2014)
Background: Nutritional deficiency during pregnancy in rural India is common. The nutritional requirements during pregnancy are increased and on the other hand the dietary intake decreases because of symptoms related to pregnancy. This adversely affects the weight of newborn. In developing countries low birth weight is major problem. So this study concern to determine the nutritional status of pregnant women and its effect on birth weight of newborn. Methods: A cross section descriptive study was conducted from Oct 2011 to May 2012 at Sarojni Nagar PHC, Lucknow, Uttar Pradesh over 323 pregnant women. They were interviewed regarding their dietary intake (on the basis of 24 hours recall method) during pregnancy. Of these 323 pregnant women, 291 could be followed up and amongst these 287 pregnant women delivered a live baby. The birth weight was measured immediate after birth. Results: In this study mean energy, protein, iron and calcium intake during pregnancy were 2013.3 ± 327.6 cal/day, 57.8 ± 11.4 gm/day, 30.15 ± 5.57 mg/day and 910.7 ± 210.4 mg/day respectively, whereas the mean intake of vitamin A, thiamine, riboflavin, niacin, vitamin C and folic acid were 608.4±161.2 μg, 1.2±0.2mg, 1.6±0.2mg, 11.9±2.1mg, 113.3 ±2.1mg and 196.2±38.4μg respectively. Nutritional deficiency during pregnancy was positively related with low birth weight. Conclusion: In the rural setup of India majority of the pregnant women were having inadequate dietary intake. Hence, policies related to maternal nutrition should be made so as to decrease the prevalence of low birth weight. DOI: http://dx.doi.org/10.3126/ajms.v6i1.9473 Asian Journal of Medical Sciences Vol.6(1) 2015 67-70